The Environmental Impact on Human Wellbeing: A Case Study on Residences in Quarry Area - Ahmad Zawawi, Emma Marinie; Wan Ibrahim, Wan Hasmirah (International Journal of Sustainable Construction Engineering and Technology, 2021)
An Environmental Impact Assessment (EIA) is compulsory in all types of new development. EIA is important to ensure that biological diversity is maintained and that development will not have any affect on the people and other species in that area. The aim of this study is to investigate the environmental impact on human wellbeing in the vicinity of quarrying. It will increase the awareness of the local population of the important factors that might affect the quality of their lives. A set of questionnaires was distributed to the community at Bandar Saujana Putra and Taman Kajang Perdana, in Selangor. A total of 60 residents were involved in the study. The results reveal that the community was concerned about health conditions and safety. However, there is still a lack of strategies to mitigate the problem. This study provides suggestions for mitigation that could be considered by the residents to reduce the effect of poor air quality caused by incorrect control and monitoring of activities in the area. It is anticipated that this study could assist both residents and authorities in improving the quality of the air as well as the residents’ quality of life.